THE EFFECT OF JIGSAW TECHNIQUE ON THE SECOND YEAR STUDENTS’ ABILITY IN COMPREHENDING NARRATIVE TEXTS AT SMP TELEKOMUNIKASI PEKANBARU - Miftahul Jannah; Fadly Azhar; M Syarfi M Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This pre-experimental research was aimed at finding out whether there was a significant effect of jigsaw technique on the second year students’ ability in comprehending narrative texts at SMP Telekomunikasi Pekanbaru. The research design was one group pre-test post-test design. The population was the second-year students in academic year 2018/2019. The sample was 25 students out of the population, chosen by cluster sampling. The instrument used to collect the data was a reading test. The tests consisted of 40 items. The obtained data was analyzed by using SPSS version 23.0. The finding of the research showed that the mean score of post-test was higher than pre-test (80.5>65.6). The value of t-test was higher than t-table (13.616>2.06) at 5% of significance level. Therefore, alternative hypothesis (Ha) was accepted. This means that Jigsaw Technique was effective for teaching reading comprehension concerning narrative text. There is a significant effect of jigsaw technique on the second year students’ ability in comprehending narrative texts at SMP Telekomunikasi Pekanbaru.Keywords: Jigsaw Technique, Reading Comprehension, Narrative Texts